2020
DOI: 10.1111/his.14048
|View full text |Cite
|
Sign up to set email alerts
|

Luminal A versus luminal B breast cancer: MammaTyper mRNA versus immunohistochemical subtyping with an emphasis on standardised Ki67 labelling‐based or mitotic activity index‐based proliferation assessment

Abstract: Aims: Proliferation assessment by the use of Ki67 is a crucial component in intrinsic subtyping of luminal breast cancers (BCs), but suffers from variability between laboratories, observers, and methods. Mam-maTyper is a quantitative molecular tool that measures mRNA levels of ERBB2, ESR1, PGR and MKI67 in BC, and interprets the results according to the St Gallen 2013 consensus recommendations. We compared MammaTyper with immunohistochemistry (IHC)-based subtypes, with a focus on standardised proliferation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Another study comparing microarray data with IHC confirm in a series of 520 samples 26 . These results are in contradiction with those observed by Finsterbusch et al 27 . These authors found a strong correlation between Ki67 in IHC and mRNA level of Ki67 obtained by Mammatyper in 101 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study comparing microarray data with IHC confirm in a series of 520 samples 26 . These results are in contradiction with those observed by Finsterbusch et al 27 . These authors found a strong correlation between Ki67 in IHC and mRNA level of Ki67 obtained by Mammatyper in 101 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The number of KI67 positive cells in tumor sections was detected using immunohistochemistry as previously reported. 17 Briefly, tumor tissue sections were deparaffinized, rehydrated, and then incubated at 95°C in citrate buffer for 20 min for antigen retrieval. At room temperature, nonspecific binding was blocked with 10% normal goat serum for 30 min.…”
Section: Immunochemistrymentioning
confidence: 99%
“…GATA6-AS1 overexpression has been reported in a literature to significantly inhibit GC proliferation and EMT. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] As a consequence, we used RT-qPCR to detect the expression of GATA6-AS1 in tumor tissues and paracancerous tissues in 45 GC patients, and found that GATA6-AS1 was significantly lower in GC tissues (Figure 6C). We subsequently verified the binding relationship between GATA6-AS1 and miR-582 by dual luciferase experiments.…”
Section: Gata6-as1 Regulates Mir-582 Expression In Gc Cellsmentioning
confidence: 99%
“…Luminal A and B are two relatively mild molecular subtypes of BRCA with better prognoses, and both are sensitive to endocrine therapy. The level of Ki67-labeled standardized proliferation is the most significant feature to distinguish the two ( 9 ). HER2-positive BRCA is characterized by its high invasiveness and high recurrence, with increased incidence year by year.…”
Section: Introductionmentioning
confidence: 99%